2005
DOI: 10.1002/pssa.200409084
|View full text |Cite
|
Sign up to set email alerts
|

Studies on electron beam evaporated ZrO2/AlGaN/GaN metal–oxide–semiconductor high‐electron‐mobility transistors

Abstract: Metal–oxide–semiconductor high‐electron‐mobility transistors were demonstrated on AlGaN/GaN with electron beam (EB) evaporated ZrO2. The composition of the EB deposited ZrO2 thin films was confirmed using X‐ray photoelectron spectroscopy (XPS). The fabricated ZrO2‐based MOSHEMTs exhibited high positive gate voltage of operation up to +7 V with low gate leakage current. For a comparison, conventional high‐electron‐mobility transistors (HEMTs) were also fabricated with identical device dimensions. The maximum dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 11 publications
(14 reference statements)
0
43
0
Order By: Relevance
“…The observation of high current collapse and gate leakage in Conv. HEMTs is due to the presence of a high interface trap density of ~1×10 13 cm −2 eV -1 at the Schottky gate/GaN interface which was determined using Eq. (2) [23],…”
Section: Structure and Fabrication Of Devicementioning
confidence: 99%
See 1 more Smart Citation
“…The observation of high current collapse and gate leakage in Conv. HEMTs is due to the presence of a high interface trap density of ~1×10 13 cm −2 eV -1 at the Schottky gate/GaN interface which was determined using Eq. (2) [23],…”
Section: Structure and Fabrication Of Devicementioning
confidence: 99%
“…Secondly, the high gate leakage currents that the conventional GaN HEMTs with Schottky metal gates suffer from, that limits the gate voltage swing and thus affecting the maximum output power as well the microwave performance [4,5]. To reduce the gate leakage currents, researchers have tried various gate dielectrics such as SiO 2 [6,7], SiN [8,9], Al 2 O 3 [10], MgO [11], Sc 2 O 3 [12], and ZrO 2 [13]. Among these, the atomic layer deposited (ALD) Al 2 O 3 is one of the most preferred gate dielectric schemes for GaN MISHEMTs [14][15][16][17] with its additional advantages such as wide band gap energy (9 eV), large dielectric constant (k ~ 10), high breakdown field (~10 MV/cm), high thermal and chemical stability.…”
Section: Introductionmentioning
confidence: 99%
“…This effect is also described as dynamic behavior degradation, gate lag, drain lag, etc., which is caused by the charge trapping effect on the AlGaN surface especially in the access region between gate and drain [4][5][6]. In order to solve these two issues, the deposition of oxide-based dielectric such as SiO 2 [7], Al 2 O 3 [8], LaLuO 3 [9], and SrO 2 [10,11] and dielectric stack such as SiN/Al 2 O 3 [12] as gate dielectric layer and passivation layer in the access region simultaneously is widely adopted. But it has been revealed that the introduction of oxide-based dielectric is likely to form Ga-O bond which is thought as one of interface sources leading to current collapse [13].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, when the thickness of SiO 2 is increased in order to decrease the gate leakage current, the gate capacitance becomes low. The efficiency of controlling the carrier density in the channel by the gate voltage is lowered, and the gain of the HEMT worsens with increasing SiO 2 thickness.Recently, MIS-HEMTs using high-k material as the insulating film have been reported [4][5][6][7]. The high-k insulation film can be thickened without reducing the gain of the HEMT.…”
mentioning
confidence: 99%